OS DIREITOS FUNDAMENTAIS DA PESSOA COM DEFICIÊNCIA E AS POLÍTICAS PÚBLICAS COMO CONCREÇÃO DA CIDADANIA (Anais do Congresso Brasileiro de Processo Coletivo e Cidadania, 2022)
The concepto of  People with Disabilities (PCD) has evolved over time, and wuth it, public policies have emerged aimed at guaranteeing more specific rights and duties, aiming at equal treatment to the extent of their equality. In this scenario, the presente work aims to analyze the fundamental rights of people with disabilities in light of the Federal Constitution of 1988, sparse legislation and current public policies, its effectiveness and chaaracteristics, identifying access for the full exercise of citizenship in a fair manner and egalitarian.